Integrated nutrient recycling: Ammonia recovery from thermophilic composting of shrimp aquaculture sludge via self-heated bench-scale reactor and mango plant growth enhancement by the compost - Tie, Hieng Ong; Che Man, Hasfalina; Koyama, Mitsuhiko; Syukri, Fadhil; Md. Yusoff, Fatimah; Toda, Tatsuki; Nakasaki, Kiyohiko; Mohamed Ramli, Norulhuda (Elsevier, 2024)
Due to the rapid growth of the aquaculture industry, large amounts of organic waste are released into nature and polluted the environment. Traditional organic waste treatment such as composting is a time-consuming process that retains the ammonia (NH3) in the compost, and the compost produced has little economic value as organic fertilizer. Illegal direct discharge into the environment is therefore widespread. This study investigates the recovery of NH3 through thermophilic composting of shrimp aquaculture sludge (SAS) and its application as a soil conditioner for the growth of mango plants. A maximum composting temperature of 57.10 °C was achieved through self-heating in a 200 L bench-scale reactor, resulting in NH3 recovery of 224.04 mol/ton-ds after 14 days. The addition of calcium hydroxide and increased aeration have been shown to increase NH3 volatilization. The recovered NH3 up to 3 kg-N can be used as a source of clean nitrogen for high-value microalgae cultivation, with a theoretical yield of up to 34.85 kg-algae of microalgae biomass from 1 ton-ds of SAS composting. Despite the high salinity, SAS compost improved mango plant growth and disease resistance. These results highlight the potential of SAS compost as a sustainable source of clean nitrogen for microalgae cultivation and soil conditioner, contributing to a waste-free circular economy through nutrient recycling and sustainable agriculture. © 2024 Elsevier Ltd